Contents of exosomes derived from adipose tissue and their regulation on inflammation, tumors, and diabetes - Wang, Yanwen; Li, Qingfeng; Zhou, Shuangbai; Tan, Pohching (Frontiers in Endocrinology, 2024)
Adipose tissue (AT) serves as an energy-capacitive organ and performs functions involving paracrine- and endocrine-mediated regulation via extracellular vesicles (EVs) secretion. Exosomes, a subtype of EVs, contain various bioactive molecules with regulatory effects, such as nucleic acids, proteins, and lipids. AT-derived exosomes (AT-exos) include exosomes derived from various cells in AT, including adipocytes, adipose-derived stem cells (ADSCs), macrophages, and endothelial cells. This review aimed to comprehensively evaluate the impacts of different AT-exos on the regulation of physiological and pathological processes. The contents and functions of adipocyte-derived exosomes and ADSC-derived exosomes are compared simultaneously, highlighting their similarities and differences. The contents of AT-exos have been shown to exert complex regulatory effects on local inflammation, tumor dynamics, and insulin resistance. Significantly, differences in the cargoes of AT-exos have been observed among diabetes patients, obese individuals, and healthy individuals. These differences could be used to predict the development of diabetes mellitus and as therapeutic targets for improving insulin sensitivity and glucose tolerance. However, further research is needed to elucidate the underlying mechanisms and potential applications of AT-exos.